Standard‐space atlas of the viscoelastic properties of the human brain - Hiscox, Lucy V.; McGarry, Matthew D. J.; Schwarb, Hillary; Van Houten, Elijah E. W.; Pohlig, Ryan T.; Roberts, Neil; Huesmann, Graham R.; Burzynska, Agnieszka Z.; Sutton, Bradley P.; Hillman, Charles H.; Kramer, Arthur F.; Cohen, Neal J.; et al. (Human brain mapping, 2020)
Standard anatomical atlases are common in neuroimaging because they facilitate data analyses and comparisons across subjects and studies. The purpose of this study was to develop a standardized human brain atlas based on the physical mechanical properties (i.e., tissue viscoelasticity) of brain tissue using magnetic resonance elastography (MRE). MRE is a phase contrast‐based MRI method that quantifies tissue viscoelasticity noninvasively and in vivo thus providing a macroscopic representation of the microstructural constituents of soft biological tissue. The development of standardized brain MRE atlases are therefore beneficial for comparing neural tissue integrity across populations. Data from a large number of healthy, young adults from multiple studies collected using common MRE acquisition and analysis protocols were assembled (N = 134; 78F/ 56 M; 18–35 years). Nonlinear image registration methods were applied to normalize viscoelastic property maps (shear stiffness, μ, and damping ratio, ξ) to the MNI152 standard structural template within the spatial coordinates of the ICBM‐152. We find that average MRE brain templates contain emerging and symmetrized anatomical detail. Leveraging the substantial amount of data assembled, we illustrate that subcortical gray matter structures, white matter tracts, and regions of the cerebral cortex exhibit differing mechanical characteristics. Moreover, we report sex differences in viscoelasticity for specific neuroanatomical structures, which has implications for understanding patterns of individual differences in health and disease. These atlases provide reference values for clinical investigations as well as novel biophysical signatures of neuroanatomy. The templates are made openly available (github.com/mechneurolab/mre134) to foster collaboration across research institutions and to support robust cross‐center comparisons. Tissue mechanical properties provide a macroscopic representation of the microstructural constituents of soft biological tissue. In the work, we have produced the first standard‐space atlas description of the stiffness and damping ratio of the healthy human brain. The detailed nature of the new atlas has revealed that neuroanatomical structures possess distinct mechanical characteristics and that sex differences exist in a range of brain structures. Our results provide a novel biophysical signature of the brain and have implications for understanding individual differences in both health and disease.